1999
DOI: 10.1093/bja/82.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of re-expansion of atelectasis during general anaesthesia

Abstract: A major cause of impaired gas exchange during general anaesthesia is atelectasis, causing pulmonary shunt. A 'vital capacity' (VC) manoeuvre (i.e. inflation of the lungs up to 40 cm H 2 O, maintained for 15 s) may re-expand atelectasis and improve oxygenation. However, such a manoeuvre may cause adverse cardiovascular effects. Reducing the time of maximal inflation may improve the margin of safety. The aim of this study was to analyse the change over time in the amount of atelectasis during a VC manoeuvre in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(141 citation statements)
references
References 29 publications
(32 reference statements)
3
117
1
20
Order By: Relevance
“…Studies have examined the peak pressure and duration of a DI required to completely overcome the atelectasis encountered in normal subjects during general anesthesia (29,30). Still other studies utilizing computed tomography of the chest have demonstrated lasting improvements after RMs, again in healthy human subjects during general anesthesia (31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined the peak pressure and duration of a DI required to completely overcome the atelectasis encountered in normal subjects during general anesthesia (29,30). Still other studies utilizing computed tomography of the chest have demonstrated lasting improvements after RMs, again in healthy human subjects during general anesthesia (31).…”
Section: Discussionmentioning
confidence: 99%
“….............................................................................................................................................................................................................. ................................................................................................................................................................................................................... ventilatory cycle, the extent depending on the relationship between the pulmonary condition and the ventilator setting [11,17,26,29,48]. Lung consolidation in the ICU is not only caused by high F i O 2 and gravitational forces as during anaesthesia, but also by surfactant dysfunction and alveolar flooding due to an altered vascular barrier [49,50] [12,[51][52][53][54][55][56].…”
Section: Human Studiesmentioning
confidence: 99%
“…[37][38][39][40] The effectiveness of PEEP in recruiting alveolar tissue correlates with the value of the Lower Inflexion Point (LIP). 13,[40][41] A range of ventilators have software suitable to measure P-V curves. A method of determining an appropriate figure for SI was calculated by Qiu and colleagues based upon 5 X Mean Airway Pressure (MAP).…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%
“…Two studies have confirmed the effective use of PV loops to reflect recruitment above the LIP and below the UIP in adult populations. [41][42] However a study by Pestana and colleagues found that P-V curves rarely reflected recruitment manoeuvres in ARDS patients which they suggest limits their application in the clinical setting as a measure of recruitment efficacy or as a guide to manage ventilation. 43 Two studies caution clinicians against using inbuilt ventilator P-V software as they had significant deleterious results in their research.…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%